2015
DOI: 10.1002/jcb.25121
|View full text |Cite
|
Sign up to set email alerts
|

bZIP17 and bZIP60 Regulate the Expression of BiP3 and Other Salt Stress Responsive Genes in an UPR‐Independent Manner in Arabidopsis thaliana

Abstract: Plants can be severely affected by salt stress. Since these are sessile organisms, they have developed different cellular responses to cope with this problem. Recently, it has been described that bZIP17 and bZIP60, two ER-located transcription factors, are involved in the cellular response to salt stress. On the other hand, bZIP60 is also involved in the unfolded protein response (UPR), a signaling pathway that up-regulates the expression of ER-chaperones. Coincidentally, salt stress produces the up-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…The diagram illustrates that in addition to IRE1, bZIP28 and bZIP60, also bZIP17 plays a role in the control of UPR target genes in Arabidopsis, as recently proposed [27]. A role for the beta subunit of the heterotrimeric G-protein complex, AGB1, in modulating the UPR has also been reported [17••,53].…”
Section: Figurementioning
confidence: 63%
See 2 more Smart Citations
“…The diagram illustrates that in addition to IRE1, bZIP28 and bZIP60, also bZIP17 plays a role in the control of UPR target genes in Arabidopsis, as recently proposed [27]. A role for the beta subunit of the heterotrimeric G-protein complex, AGB1, in modulating the UPR has also been reported [17••,53].…”
Section: Figurementioning
confidence: 63%
“…The evidence that plant-specific NAC TFs have a role in stress responses support that in addition to common routes plants have evolved unique strategies for ER stress defense that, as in the case of NAC062, may also depend on the activity of TFs that are localized to the membrane organelles other than the ER. Interestingly also, it has been recently suggested that unspliced AtbZIP60 may have a role in modulating the expression of BiP3 in conditions of ER stress [27]. Phosphorylation of the elf2α may occur in a hypothetical PERK-like pathway for ER stress responses.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that bZIP60s are important plant transcription factors that participate in the expression and regulation of ER stress-related and other genes in Arabidopsis (Sabrina et al, 2012; Henriquez-Valencia et al, 2015). The results of this study showed that both TabZIP60B and TabZIP60D respond to osmotic stress very quickly.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for the accumulation of unspliced BdbZIP60 in ER stress conditions in Brachypodium is that ER stress may induce BdbZIP60 transcription to levels that overcome the RNase activity of IRE1 to lead to a translated form of BdbZIP60 with specific roles in stress responses. For example, it has been suggested that the unspliced form of AtbZIP60 in Arabidopsis may have a role in salt-stress response (Henriquez-Valencia et al 2015; Parra-Rojas et al 2015). Analogously it is possible that the Brachypodium UPR also relies on the translated unspliced BdbZIP60.…”
Section: Discussionmentioning
confidence: 99%